Effect of Health Education about Baby Massage to Parentings Skills at Bidan Praktik Mandiri Anita Pera Simalingkar B Medan - Kristina, Ingka; Simanullang, Ester; Simbolon, Marlina (Sari Mutiara Indonesia University Press, 2018)
Massage is a massage that was done by touching the skin (stimulus touch), done by using hand to produce effects, nerves, muscles, respiratory system and blood circulation and limpha and increase compassion between mother and baby. Knowledge about baby massage is not widely found of public because lack of knowledge and only be done by traditional healers and health workers, even though baby massage can be done by anyone, including parents. The purpose of this research was to find the effect of health education about a baby massage on parenting skills. Parents are an important container for infant growth and development. Baby massage needs to be known by the public, especially parents who have babies. During this time, baby massage is considered only to be done by traditional healers and health workers, even though the baby massage can be done by anyone, including the parent. Designused was a pre-test post-test without a control group test to see the effect of health education about a baby massage on parenting skills. The research sample conducted in 32 respondents using purposive sampling technique. The measuring instrument used is the Standard Operating Procedure (SOP). The results of bivariate analysis were tested using Wilcoxon test with a significance level of 5% with a value of p <0.05 which was 0.014. The mean rank value is 3.50. The conclusion of this research is that there is an influence of health education about a baby massage on parenting skills, therefore it is necessary to carry out sustainable health education to parents so that they can improve the ability of parents to do baby massage.